Oligarchie – eine Form bürgerlicher Herrschaft: Das Beispiel osteuropäischer semi-peripherer Kapitalismus - Becker, Joachim (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2015)
The close link between economic and political power is the key characteristic of oligarchic rule. Different forms of oligarchic rule and structures have emerged during the capitalist transformation in Eastern Europe over the last 25 years. The article compares oligarchic rule in the successor states of multinational federations that disintegrated after 1989 – i.e. the Soviet Union, Yugoslavia and Czechoslovakia. From a comparative perspective, it analyses the emergence of domestic oligarchic groups, the (sub-)sectors of their economic activities and their relationship to the semi-peripheral states (in particular their relationship with political parties as a key transmission belt into state decision-making centres).